Clonal propagation of Stevia (Stevia rebaudiana Bertoni) advanced lines in a Temporary Immersion Bioreactor System - Tapia y Figueroa, María de Lourdes (2022)
Stevia (Stevia rebaudiana A Bertoni), is a native species from Paraguay and Brazil, which is used as a natural sweetener with medicinal value in the preparation of beverages, sweets and others. Its propagation through sexual seeds is limited by their poor quality, for this reason its asexual propagation is promoted through different in vitro techniques. In the present investigation, the response of three genotypes of stevia to propagation in Temporary Immersion Bioreactor (TIB) System was studied with four different media as a treatments. The results showed that the treatment M2 (MS + 1 mg/L BAP + 0.1mg/L NAA + 30 g Sucrose) gave the best results for all evaluated characteristics with the exception of the number of rootlets/seedling and being the treatment M1 (MS without growth regulators + 30 g of Sucrose) achieved the highest number of roots and good values for the other characteristics. High quality plants were achieved and the genotype that responded best was IBT-1, and in the acclimatization phase a high survival rate was obtained.